Heutagogical Approach in Indonesian Islamic EFL Classrooms: Exploring Students’ Readiness and Attitudes - Muhammad Iksan; Muhammad Basri; Sahril Nur (Eduvelop: Journal of English Education and Development, 2026)
Heutagogy is a self-regulated learning process where students have a higher level of control and autonomy in their learning processes. Heutagogy is different from traditional learning approaches, which have been widely practised in Indonesian EFL settings. The study aims to explore students' readiness and attitude in applying heutagogy in EFL settings at an Indonesian Islamic university. The study uses a mixed-methods approach. The participants consisted of 201 English language learners, and both a survey and interviews were conducted. The results from the survey were analysed by employing descriptive statistics, and the results from the interviews were analysed to gain a deeper understanding of students' experiences and their perspectives on self-directed learning. The findings from the study show that, despite the students’ enthusiasm, creativity, and teamwork, they face challenges in the processes of self-assessment, self-directed learning, and time management. The applicability of heutagogy-based learning approaches in the real world is limited by the rigid structure of the curriculum and the typical relationships between the tutors and the students. The students’ need for flexibility and innovation in the learning environment is apparent, despite the challenges they face in the process of accepting self-directed learning. This paper concludes that the step-by-step process of applying heutagogical principles through scaffolding and blended learning approaches is necessary for the effective application process within the context of the English as a foreign language educational program. Organised intervention approaches, such as the development of self-assessment skills, may help the process towards increased learner autonomy for the students. The results have contributed to the ever-growing literature related to the application of heutagogy in English foreign language educational contexts.